Exploring Gender Education and Sexuality Awareness in Children of Single-Parent Families - Tarisa Tarisa; Syafruddin Syafruddin; Nursaptini Nursaptini; Hamidsyukrie Hamidsyukrie (LPPM IAIN Parepare, 2024)
The purpose of this study was: (1) to identify and analyze patterns of gender education in children in single-parent families; (2) to identify and analyze patterns of sexuality education in children in single-parent families. The research uses a qualitative approach case study method. Data collection is done through observation, interviews, and documentation. Data analysis techniques in this study use qualitative data analysis techniques with the process of data reduction, data presentation, and drawing conclusions. The results found (1) The pattern of gender education in children in single-parent families in East Aikmel Village uses methods / patterns of treatment shown through providing full access and support to children in every positive activity without gender restrictions, children are prohibited from committing physical violence and being rude to their playmates, children are asked to love and respect each other between siblings; (2) The dominant pattern of sexuality education in children in single-parent families in East Aikmel Village is the pattern of limb recognition, which is shown through single parent, teaching children the function and how to use the left and right hands appropriately, teach children private body parts such as buttocks, chest, and genitals, teach boys if they want to pee then the penis will become tense, and provide illustrations to dolls and show body parts to dolls that must be covered and guarded.